PENGARUH PEMBERIAN EKSTRAK ETANOL PEGAGAN (Centella asiatica sp.) TERHADAP MEMORI PASCASTRES LISTRIK KRONIK Kajian pada Tikus Putih (Sprague dawley) dengan Dosis 150 mg/kgBB dan 300 mg/kgBB selama Empat Minggu dengan Parameter Waktu (Escape Latency Time) pada Uji Morris Water Maze - , SHINTA SEPTIARINA, dr. Dwi Cahyani Ratna Sari, M.Kes,.P.A (K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Pegagan has neurotropic and neuroprotective effects. Objective: To know the effect of pegagan (Centella asiatica sp.) in improving memory after electrical stress induction. Materials and Methods: This study used pre and post controled group design. Fifthteen male rats (Sprague dawley), aged 4 weeks and Â±100 gram weight were divided randomly into 3 groups, two treated groups and one controled group. Treated groups were given ethanolic extract of pegagan with doses of 150 mg/KgBB (KP1) and 300 mg/kgBB (KP2), and controled group was given aquades(KN) by oral for 28 days. Every rats were given electrical stress induction for 10 minutes every day. The rats were tested with Morris Water Maze (MWM) twice daily for 6 days. The scoring parameter of rats performance was based on the average time taken to reach the platform (escape latency time). Kruskal-Walish test was used to know the differences of memory between treated and controled group. Result: The results showed that the average of escape latency time in rats KN, KP1, KP2 groups were 8,77Â±0,297